مقالہ نگاری کے مختلف مراحل :کتب تحقیق کی روشنی میں تجزیاتی مطالعہ: Different stages of Thesis writing: An Analytical Study in the light of Research Books - Dr. Zill e Huma (Al Manhal Research Journal, 2024)
No one can deny the importance of research. Our religion Islam has ordered us to research in every matter. Allah Almighty says in Holy Quran: "يٰاَيُّهَا الَّذِيْنَ اٰمَنُوْا اِنْ جَآءَكُمْ فَاسِقٌ بِنَبَاٍ فَتَبَيَّنُوْا" In the same way the Holly Prophet (P.B.U.H) said: “كَفَى بالمَرْءِ كَذِبًا أَنْ يُحَدِّثَ بِكُلِّ مَا سَمِعَ Research holds the key to knowledge expansion. It opens doors to new possibilities and reveals strategies to solve complex problems. It can enhance the ability of the students to come up with information about a topic by deeply investigating the subject matter. Every researcher has to pass through a systematic process during his/her research of BS, MS or PhD There are many different stages of thesis writing. Expertise of research have mentioned these stages in their books. This article deals with these different stages of thesis writing.